The Influence of Manager’s Trustworthiness on Subordinate’s Trust in the Manager - Vaida Kameneckienė (Jaunųjų Mokslininkų Darbai, 2022)
Trust in the organization makes the leadership for the manager easier, contributes to the achievement of the goals. Real and sustainable trust determines the reliability of the entire organization and supports the corporate reputation. A person’s trust in another person eventually leads to the trust of the entire system. Behaviour is a significant determinant of organizational trust. The strongest relationship is between the trustworthiness of the manager and the trust of the subordinate. However, previous studies lack the dimensions of trust. Therefore, in this study, research on the influence of the trustworthiness of the manager on the trust of the subordinate in the manager includes dimensions of each key concept. The purpose of the study is to determine the influence of the trustworthiness of the manager on the subordinate’s trust in the manager. A theoretical model as a background of the research is presented. It is composed of five dimensions of the trustworthiness of the manager, that is, consistency of manager behaviour, integrity of behaviour, sharing of control, and communication and demonstration of concern, and their influence on the general trust, as well as cognitive and emotional trust of subordinates in the manager.